Cren??as de autoefic??cia e apoio social na transi????o para a doc??ncia - Araujo, Leidiane Almeida (2015)
It was proposed in the present study to investigate the relationship between perceptions of teacher self-efficacy and social emotional support of graduating students of pedagogy and beginner teachers in early childhood education or in the early years of elementary school. The teaching self-efficacy refers to the teacher's confidence in their own abilities to perform teaching activities associated with perceived social support that can help the adaptation of the individual during the transition to teaching. It is understood that this transition is not finished with the completion of graduation, it extends until the first years of teaching practice. The total sample consisted of 281 participants. The scale was composed of three parts: [1] Teacher Beliefs Scale - short version, [2] Inventory of Emotional Support in the Transition to Teaching (IAETD) and [3] Participants Characterization Questionnaire. The results obtained by means of confirmatory factor analysis indicated evidence of instrument validity and good internal consistency in the factors. The better adjusted models presented the teacher's self-efficacy in three factors: efficacy in instructional strategies (EIS) effectiveness in managing classroom (EMC) and efficacy in student engagement (ESA); the social and emotional support to two factors: emotional support and professional support. It was found that training in public or private institutions does not imply distinctions in perceptions of the teacher self-efficacy and the social emotional support for both groups. However, when related to sex, women had greater efficacy in student engagement than men in both groups. Among teachers, those without postgraduate degrees demonstrated higher self-efficacy to motivate students than teachers with postgraduate degrees. Teachers with plans to stay in teaching careers felt themselves more professionally supported than those with plans to switch careers. It was also found that the older the teachers, the lower the self-efficacy for managing the classroom and lower the perception of professional support. In the group of students, the ones who were working were perceived to be more effective in managing the classroom than students that were not working. Finally, the weak relationships between the variables of teacher self-efficacy and social emotional support in both groups reinforced the prospects of the multidimensionality of these phenomena, indicating that other factors are combined in this relationship in the transition to teaching. Along these lines, new studies can address the dynamics and direction of these relationships in the development of teachers.